Pengembangan desa budaya dan pembuatan pupuk cair sabut kelapa di Desa Brosot, Galur, Kulon Progo - Paramita, Brigitta Laksmi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Real Lecture activities Atma Jaya Yogyakarta start from August to January 2021. The 80 KKN implementation is carried out in various areas in Yogyakarta such as Kulonprogo Regency and Gunung Kidul Regency. The location for the implementation of KKN 80 unit P Group 77 provides innovations that are in accordance with the potential of Brosot Village. Broadly speaking, Brosot Village has two divisions of village potential, namely culture and tourism. There are various forms of cultural potential ranging from social order, customs, and traditions, dance dramas, gamelan jathilan and shalawatan, the players from children to adults. While the tourism potential has Tresik beach which can be used as tourism to be developed such as a unique and rare turtle breeding place. The results obtained and processed for future development of Brosot Village are the development of village potential in the field of entrepreneurship by managing coconut fiber into liquid organic fertilizer (POC).